Podejmowanie decyzji inwestycyjnych w instytucjach ubezpieczeniowych w świetle koncepcji finansów behawioralnych - Czerwińska, Teresa Tatiana (Investment Decision Making of the Insurance Companies and Pension Funds - the Idea of Behavioural Finance, 2008)
The managers of insurance companies and pension funds are convinced about necessaries of undertaking investment decisions rationally, so they place in the statutes of the institution regulative rules. On the other side, making decision in the uncertainty and risks conditions assume working out less formal rules. The author considers the process of investment decisions making by insurance companies and pension funds in the wide specter of qualitative factors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 54-61